Feasibility study on the use of UV/Vis spectroscopy to measure total phenolic compound and pH in apple (Malus sylvestris L.) cv. Manalagi. Issue 1 (April 2020) - Iqbal, Z; Kamal, M A; Komariyah, A N; Adiyaksa, I P; Argo, B D; Wibisono, Y; Damayanti, R
Abstract: This paper will report the feasibility study on the use of UV/Vis spectroscopy to determine apple quality based on Total Phenolic Compound (TPC) and pH. To achieve the conclusion, several stages had to be conducted. First, the total 50 sample of apples from 4 different ripening stages (3, 4, 5 and 6 month) were collected from local farmer in Bumiaji District and extracted. The juice from extraction was prepared for UV/Vis spectrum collection ranging from 200-1100 nm. TPC and pH were then measured. Afterwards, chemometrics analysis was performed to provide Partial Least Square (PLS) prediction model. And lastly, was identifying robustness of the model by analysing all the statistic parameter. The result showed that, partial spectrum of PLS model to predict absorbance of TPC provided good determination coefficient (R 2 calibration was 0.803 and R 2 validation was 0.710) while RMSEC and RMSECV were 0.070 and 0.088 respectively. As for pH model prediction, the best model was also obtained from the partial spectrum resulting R 2 calibration was 0.822 and R 2 validation was 0.797 while RMSEC and RMSECV were 0.56 and 0.61, respectively.